(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study was carried out with the objectives to find out the development and sensory evaluation of value-added Muffin. The product prepared were “Muffin” by incorporation of Multigrain flour and Herbal extracts (curry leave and basil leave extract) in different proportions T1 65:35:40:35, T2 50:50:50:45, T3 35:65:60:55 and T4 30:80:70:65 respectively T0, 100g of refined flour without incorporation of Multigrain flour and herbal extracts served as control. The products were sensory evaluation by using 9- point Hedonic scale. The data obtained during study were analysed statistically using analysis of variance (ANOVA) and C.D techniques. It was concluded that after sensory evaluation best treatment T3 had highest score with regards overall acceptability contains Refined flour 35 g + Multigrain Flour 65g + Basil leaves extract 55 ml + Curry leaves extract 65 ml. On the basis of findings it was concluded that Multigrain flour and herbal mix can be incorporate successfully in the “Muffin” as well as colour, taste and flavour enhancer.